2014
DOI: 10.1261/rna.047910.114
|View full text |Cite
|
Sign up to set email alerts
|

WBSCR22/Merm1 is required for late nuclear pre-ribosomal RNA processing and mediates N7-methylation of G1639 in human 18S rRNA

Abstract: Ribosomal (r)RNAs are extensively modified during ribosome synthesis and their modification is required for the fidelity and efficiency of translation. Besides numerous small nucleolar RNA-guided 2 ′ -O methylations and pseudouridinylations, a number of individual RNA methyltransferases are involved in rRNA modification. WBSCR22/Merm1, which is affected in WilliamsBeuren syndrome and has been implicated in tumorigenesis and metastasis formation, was recently shown to be involved in ribosome synthesis, but its … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
109
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 127 publications
(111 citation statements)
references
References 41 publications
2
109
0
Order By: Relevance
“…In agreement with this hypothesis, investigators have observed retention of fluorescently labeled pre-40S in the nucleus upon WBSCR22 depletion (Wild et al. , 2010), and the 3′-extended forms of 18S-E that accumulates under these conditions are reported to be nuclear (Haag et al. , 2015).…”
Section: Discussionmentioning
confidence: 99%
“…In agreement with this hypothesis, investigators have observed retention of fluorescently labeled pre-40S in the nucleus upon WBSCR22 depletion (Wild et al. , 2010), and the 3′-extended forms of 18S-E that accumulates under these conditions are reported to be nuclear (Haag et al. , 2015).…”
Section: Discussionmentioning
confidence: 99%
“…For generation of tetracycline‐inducible stable cell lines the NSUN3 or ABH1 CDS were cloned into the pcDNA5 vector with C‐terminal GFP or His‐PreScission protease cleavage site‐2×FLAG (HisPrcFlag) tag. The catalytically inactive NSUN3 C265A mutant was generated by site‐directed mutagenesis (Haag et al , 2015b). The constructs were transfected into HEK293 Flp‐In T‐Rex cells according to the manufacturer's instructions and as described (Sloan et al , 2015).…”
Section: Methodsmentioning
confidence: 99%
“…The ABH1 D233A and R233A, and NSUN3 C265A mutants were generated by site‐directed mutagenesis (Haag et al , 2015b). Recombinant proteins were expressed in Escherichia coli (DE3) Rosetta pLysS (NSUN3, ABH1) or (BL21) Codon Plus (MTIF2, TUFM) cells and details of protein purification are given in the Appendix Supplementary Methods.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A very recent report has shown that yeast and worm homologs of human NSUN5 methylate C2278 in 25S rRNA of Saccharomyces cerevisiae and C2381 in 26S rRNA of Caenorhabditis elegans; in addition, the reduction in the levels of NSUN5 homologs decreases translational fidelity in yeast and increases the lifespan of S. cerevisiae, C. elegans and Drosophila melanogaster (Schosserer et al, 2015). The human ortholog of yeast Bud23, WBSCR22 (Merm1), has also been shown to mediate N 7 -methylation of G1639 and 18S rRNA maturation in cells (Haag et al, 2015); however, little is known about the base methyltransferase of rRNA in mammals.…”
Section: Introductionmentioning
confidence: 99%